The ownership of industrial land in Russian cities: Explaining patterns of privatization across regions and firms - William Pyle (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
The voluminous literature on the privatization of Russian industry overlooks, almost completely, the story of enterprise land rights - a story that does not jibe well with the standard narrative of post-Soviet reform. This paper explains the path that has led to significant inter-regional variation in the ownership status of lands underneath urban industrial enterprises. It then introduces unique data from a survey of 359 large industrial firms across several dozen of Russia's largest cities to explore why some firms have purchased their production plots whereas others continue to lease or hold these lands under the old Soviet system of tenure. In exploring both inter-regional and inter-firm variation in land rights, we find evidence consistent with the proposition that the decisions of regional officials and (the managers and owners of) firms are guided by securing rights over real estate rents.
URN:NBN:fi:bof-201408072146
Keywords: K11; L6; P26; P31; R33; 330; urban land; property rights; Russia